A study for lens capsule tearing during capsulotomy by finite element simulation. (May 2021) - Han, Shaofeng; He, Changyan; Ma, Ke; Yang, Yang
Highlights: Combined distortion energy criterion and interface law expresses the lens capsule tearing. This work quantitatively analyzes the effect of various motion parameters on the tear force. A 2-DOF force sensing forceps (RSME = 1.47 mN) is developed to measure the tear force during capsulotomy. Simulated tear force has a good agreement with that of the capsulorhexis experiment of isolated porcine eyes. Abstract: Background and objective: During capsulotomy, the force applied to the anterior capsule is a crucial parameter controlling capsule tears, that affects the clinical performance. This study aims to investigate the tear force in capsulotomy and analyze the effects of different tearing conditions on the tear force. Methods: A three-dimensional model of the human lens was constructed based on published clinical data using the finite element (FE) method. The lens model consisted of four layers: the anterior and posterior lens capsule, the cortex, and the nucleus. Distortion energy failure criterion combined with the bilinear interface law was used to express the crack propagation process at the edge of the anterior lens capsule. At the clamping position, a local coordinate system was established to parameterize the capsule tearing. The simulation results were then validated by conducting a capsulorhexis experiment using isolated porcine eyes with force-sensing forceps. Results: The simulation results showed a good agreement with the experimental data of two porcine specimens (No. 6 and 9) during a stable tearing process ( p -values = 0.76 and 0.10). The mean force differences between the experimental data and the simulation were 3.10 ± 2.24 mN and 2.14 ± 1.73 mN, respectively. The tear direction with a minimum mean tear force was at θ 1 = 0° and θ 2 = 30°. The tear velocity was not significantly different to the variation in the tear force. However, an appropriate capsulorhexis diameter was found to contribute to the reduction of tear force. Conclusions: The outcome of this paper demonstrates that our FE model could be used in modeling lens capsule tearing and the theoretical study of tear mechanism.